1988
DOI: 10.1210/jcem-67-3-493
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of 24-Hour Growth Hormone Profiles in Children: Relation to Growth*

Abstract: The relationship between height and amount of GH measured during a 24-h period was studied in 127 children who were growing at different rates. Of the children, 88 were prepubertal (3-16 yr old) and 39 were pubertal (10-16 yr old). The height of each child was expressed as the SD score, i.e. height in relation to the sex- and age-matched Swedish reference groups, and spontaneous GH secretion was estimated by taking integrated 20-min blood samples for a 24-h period, i.e. 72 samples/child. In a few children, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(134 citation statements)
references
References 19 publications
13
118
3
Order By: Relevance
“…With this method it is possible to get an idea of true nocturnal integrated GH and ir-GHRH secretion. Discrete and integrated sampling has been compared in a recent study and no obvious blunting or widening of the peaks using an integrated sampling technique was found (24). .…”
Section: Discussionmentioning
confidence: 99%
“…With this method it is possible to get an idea of true nocturnal integrated GH and ir-GHRH secretion. Discrete and integrated sampling has been compared in a recent study and no obvious blunting or widening of the peaks using an integrated sampling technique was found (24). .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four-h endogenous GH secretion has been reported to correlate with other parameters related to growth, such as IGF-I (25), growth velocity (27), chronologic age (24), and SDS for height (28). Some authors have demonstrated correlations between UGH and IGF-I (14, 16) and UGH and growth velocity (15).…”
Section: Ugh In 24-h Day and Night Urine Samplesmentioning
confidence: 99%
“…Albertsson-Wikland and Rosberg (27) found a nonlinear correlation between ht and mean GH concentration for pubertal children (r = 0.36) but the correlation was much more striking for the prepubertal children where a linear correlation (r = 0.69) was found. A correlation of mean GH and ht was not found in our pubertal subjects, perhaps due to our small sample size or the presence of constitutional growth delay.…”
Section: Discussionmentioning
confidence: 92%